Olfactory Stimulation Successfully Improves Swallowing Function of Aged Rats Through Activating Central Neuronal Networks and Downstream DHPR–RyR-mediated Neuromuscular Activities. Issue 2 (11th August 2021) - Chen, Yea-Tzy; Chen, Li-You; Renn, Ting-Yi; Cheng, Meng-Shan; Wang, Chi-Te; Klimenkov, Igor V; Sudakov, Nikolay P; Liao, Wen-Chieh; Chen, Yea-Jyh; Chang, Hung-Ming
Abstract: Presbyphagia is age-related changes in swallowing function, which imposes a high risk of aspiration in older adults. Considering olfactory stimulation (OS) can influence behavioral activities by modulating neuronal excitability, the present study aims to determine whether OS could improve the swallowing function of aged rats through activating the central neuronal networks and downstream muscular activities participated in the control of swallowing. Aged male Wistar rats received OS by inhaling a mixture of plant-based volatile molecules twice a day for 12 days were subjected to functional magnetic resonance imaging (fMRI) and c-fos, choline acetyltransferase (ChAT) immunostaining to detect the neuronal activities of the orbitofrontal cortex (OFC) and medullary nuclei engaged in swallowing control, respectively. The functional effects of OS on downstream pharyngeal muscle activity were examined by evaluating the dihydropyridine receptor–ryanodine receptor (DHPR–RyR)-mediated intramuscular Ca 2+ expression, and analyzing the amplitude/frequency of muscle contraction, respectively. In untreated rats, only moderate signal of fMRI and mild c-fos/ChAT expression was detected in the OFC and medullary nuclei, respectively. However, following OS, intense signals of fMRI and immunostaining were clearly expressed in the orbitofronto-medullary networks. Functional data corresponded well with above findings in which OS significantly enhanced DHPR–RyR-mediated intramuscular Ca 2+ expression, effectively facilitated a larger amplitude of pharyngeal muscle contraction, and exhibited better performance in consuming larger amounts of daily dietary. As OS successfully activates the neuromuscular activities participated in the control of swallowing, applying OS may serve as an effective, easy, and safe strategy to greatly improve the swallow function of aging populations.